Projecting the fuel efficiency of conventional vehicles The role of regulations, gasoline taxes and autonomous technical change - Tikoudis, Ioannis (OECD Publishing, 2022)
The fuel efficiency of conventional private vehicles is a key input in the design of several economic and environmental policies. Reliable projections of the fuel efficiency variable can improve estimates on the future emission savings from policies promoting vehicle replacement, and on future revenues from fuel taxes. This paper examines the evolution of fuel efficiency using data on cars entering the US market from 1984 to 2020. It uses a series of new indexes for the gasoline cost in OECD countries and the stringency of fuel economy regulations. The paper shows that the effect of fuel prices and taxes is significant and robust. Doubling the user cost of gasoline with a stringent carbon tax will cause an irreversible increase in fuel efficiency by 6-11%. Increasing the stringency of the US CAFE standards by 10% raises average fuel efficiency by 2-3%. The impact of cross-market regulations is ambiguous
Keywords: Economics; Energy; Taxation; Environment; Transport